PRAKTIK SOSIAL ENTREPRENEUR GUNA PENGEMBANGAN LIFE SKILL PENYANDANG DISABILITAS DI BALAI KARYA BERKAT SALATIGA - Sari, Dwi Novita; Nugroho, Fibry Jati (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2025)
Social entrepreneurship is an innovative approach that combines social goals with entrepreneurial principles. This study aims to explore the practice of social entrepreneurship at Balai Karya Berkat Salatiga and its role in developing life skills for persons with disabilities. Using a qualitative method with a case study approach, the research found that Balai Karya Berkat Salatiga successfully created an inclusive environment that supports the economic and social empowerment of persons with disabilities. The results show that social programs in the form of entrepreneurship skills training can enhance the independence and self-confidence of persons with disabilities. These findings have significant implications for developing a sustainable community-based empowerment model.